1994
DOI: 10.1073/pnas.91.10.4155
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inhibition of superoxide dismutase produces apoptotic death of spinal neurons.

Abstract: Mutations in the gene for Cu/Zn superoxide dismutase (SOD1) have been detected in some families with an autosomal dominant form ofamyotrophic lateral sclerosis; these mutations appear to reduce the activity of this enzyme. To determine whether decreased SOD activity could contribute to motor neuron loss, SODi was inhibited chronically with either antisense oligodeoxynucleotides or diethyldithiocarbamate in spinal cord organotypic cultures. Chronic inhibition of SOD resulted in the apoptotic degeneration of spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
114
1
2

Year Published

1997
1997
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(124 citation statements)
references
References 39 publications
7
114
1
2
Order By: Relevance
“…In line with such an interpretation, melatonin prevented cell death induced by inhibition of superoxide dismutase as well as A␤-induced lipid peroxidation. Inhibition of SOD by DDTC is a well established model of oxidative injury (Omar and Pappolla, 1993) that has been used previously to induce death of spinal cord neurons via an apoptotic pathway (Rothstein et al, 1994). These observations are also in agreement with the oxidative stress hypothesis of AD.…”
Section: Discussionsupporting
confidence: 78%
“…In line with such an interpretation, melatonin prevented cell death induced by inhibition of superoxide dismutase as well as A␤-induced lipid peroxidation. Inhibition of SOD by DDTC is a well established model of oxidative injury (Omar and Pappolla, 1993) that has been used previously to induce death of spinal cord neurons via an apoptotic pathway (Rothstein et al, 1994). These observations are also in agreement with the oxidative stress hypothesis of AD.…”
Section: Discussionsupporting
confidence: 78%
“…An increased level of GSH in cells expressing Bcl-2 could account for our results because GSH plays a central role in the cellular metabolism of HNE (Ishikawa et al, 1986;Spitz et al, 1990). In studies of spinal cord organotypic cultures, Rothstein et al (1994) showed that downregulation of Cu/Zn-SOD resulted in neuronal apoptosis, which was inhibited by antioxidants. Troy et al (1996b) reported that downregulation of Cu/Zn-SOD in PC12 cells induces apoptosis, which can be prevented with inhibitors of nitric oxide synthase, suggesting the involvement of peroxynitrite.…”
Section: Discussionmentioning
confidence: 82%
“…Doses of DETC chosen for the present study were the doses shown to produce 80% to 100% inhibition of SOD activity in previous studies. 27 The dose of TEMPOL used in our experiments has been reported to induce N G -nitro-L-arginine methyl ester (L-NAME)-blockable reduction of arterial pressure. 14 A single dose of TEMPOL was used because its action duration is relatively long, as has been reported previously.…”
Section: Laser-doppler Flowmetry Of Cbf and Mbfmentioning
confidence: 99%